2014
DOI: 10.5114/amsik.2014.50531
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilaments and traumatic brain injury

Abstract: StreszczenieW neurotraumatologii medyczno-sądowej praktyczne znaczenie ma obiektywne ustalenie wieku -czasu powstania stłuczenia mózgu. Obecnie postęp immunohistochemii umożliwia badania elementów strukturalnych komórek, w tym także białek cytoszkieletu neuronu -neurofilamentów, które ze względu na swoje właściwości mogłyby zostać wykorzystane do określania wieku obrażeń mózgu w medycynie sądowej. Celem niniejszej pracy jest przegląd aktualnego piśmiennictwa pod kątem badań dotyczących zmian zachodzących w neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…the time that has lapsed since the trauma [2,13,17]. However, laboratory practice has shown that these methods are not accurate enough and therefore pose a danger of diagnostic errors.…”
Section: Introductionmentioning
confidence: 99%
“…the time that has lapsed since the trauma [2,13,17]. However, laboratory practice has shown that these methods are not accurate enough and therefore pose a danger of diagnostic errors.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical markers of structural degeneration are of value. For example, accumulation of neurofilament (33)(34)(35)(36) and proteolytic fragments of alpha spectrin, one of the proteins at the interface between the axoskeleton and the membrane (37), are reliable indicators of focal damage. Many proteins that undergo anterograde transport to the synapse accumulate can be detected by immunohistochemistry at the site of damage (38,39).…”
Section: Axon Changes Following Traumatic and Hypoxic-ischemic Brain Injurymentioning
confidence: 99%
“…Damaged nervous tissue releases various substances that may have potential as markers of the time elapsed since an injury [78]. Inflammation of the CNS after trauma is similar to that of damaged skin and skeletal muscle, whereas the local reaction (including migration of glial cells) is specific to the CNS [5].…”
Section: Brain Injurymentioning
confidence: 99%